Generation of Astrocyte-specific BEST1 Conditional Knockout Mouse with Reduced Tonic GABA Inhibition in the Brain - Joo, Jinhyeong; Kim, Ki Jung; Lim, Jiwoon; Choi, Sun Yeong; Koh, Wuhyun; Lee, C. Justin (Experimental neurobiology, 2024)
Bestrophin-1 (BEST1) is a Ca -activated anion channel known for its role in astrocytes. Best1 is permeable to gliotransmitters, including GABA, to contribute to tonic GABA inhibition and modulate synaptic transmission in neighboring neurons. Despite the crucial functions of astrocytic BEST1, there is an absence of genetically engineered cell-type specific conditional mouse models addressing these roles. In this study, we developed an astrocyte-specific BEST1 conditional knock-out (BEST1 aKO) mouse line. Using the embryonic stem cell (ES cell) targeting method, we developed floxed mice (C57BL/6JCya- /Cya), which have exon 3, 4, 5, and 6 of flanked by two loxP sites. By crossing with hGFAP-CreER mice, we generated floxed/hGFAP-CreER mice, which allowed for the tamoxifen-inducible deletion of under the human GFAP promoter. We characterized its features across various brain regions, including the striatum, hippocampal dentate gyrus (HpDG), and Parafascicular thalamic nucleus (Pf). Compared to the Cre-negative control, we observed significantly reduced BEST1 protein expression in immunohistochemistry (IHC) and tonic GABA inhibition in patch clamp recordings. The reduction in tonic GABA inhibition was 66.7% in the striatum, 46.4% in the HpDG, and 49.6% in the Pf. Our findings demonstrate that the BEST1 channel in astrocytes significantly contributes to tonic inhibition in the local brain areas. These mice will be valuable for future studies not only on tonic GABA release but also on tonic release of gliotransmitters mediated by astrocytic BEST1.